Sensorial and physicochemical qualities of pasta prepared with amaranth - Juliana Lopes dos Santos; Jamile Kailer dos Santos; Elisvânia Freitas dos Santos; Fabiane La Flor Ziegler Sanches; Maria Raquel Manhani; Daiana Novello (Universidade Estadual de Maringá, 2015)
Current assay analyzed the sensorial acceptability of pasta when amaranth flour (AF) is added at different percentages. The physical and chemical composition and the acceptance similarities of standard formulation and formulation with a greater level of AF addition were assessed. Five formulations of pasta were used: F1 standard (0% AF); F2 (20% AF); F3 (25% AF); F4 (30% AF); F5 (35% AF). Fifty-six untrained tasters, from both genders and aged between 17 and 27 years, participated in the sensorial analysis. The physicochemical analyses determined moisture content, ash, protein, fat, carbohydrates, crude fiber, and calories. F4 with the highest AF content obtained acceptance similar to the standard formulation in all attributes. In addition, F4 provided higher levels of dietary fiber, proteins, ash, calories and lipids than standard formulation. Only carbohydrates levels in F4 were lower. Current study demonstrated that pasta with the addition of up to 30% of AF was the most sensory-accepted among the AF-added pastas. Since it provided sensory acceptance similar to the standard product, good marketing expectations are given.